Metabolic Dynamics During Loquat Fruit Ripening and Postharvest Technologies - Cai, Jianghua; Chen, Tong; Zhang, Zhanquan; Li, Boqiang; Qin, Guozheng; Tian, Shiping (Frontiers in Plant Science, 2019)
Loquat is an important fruit widely cultivated worldwide with high commercial value. During loquat fruit development, ripening and storage, many important metabolites undergo dramatic changes, resulting in accumulation of a diverse mixture of nutrients. Given the value of loquat fruit, significant progresses have been achieved in understanding the metabolic changes during fruit ripening and storage, as well as postharvest technologies applied in loquat fruit in recent years. The objective of the present review is to summarize currently available knowledge and provide new references for improving loquat fruit quality.